EUROPA OCCIDENTAL Y EL DESARROLLO CHILENO 1945-973 - MACARENA CARRIÓ; JOAQUÍN FERMANDOIS (Historia (Santiago), 2003)
Good relations with the main Westeuropean powers has been the cornerstone of Chilean foreign Policy since independence. Since the Second World War, the U.S. replaced almost completely the european influence on Chilean international relations. But step by step, the European powers reconstructed the economic ties with Chile, which was their main goal. Chile's goal mainly intended to find wider markets for copper, and above all, economic assistance for development. The assistance was considered irreplaceable for the Chileans. Third, there was the larger context of the Cold War and the ideological history of the century, which colored the visions of Chileans and European alike. The visits of Frei to Europe in 1965; and the visits of General De Gaulle to Chile in 1965, and of Queen Elizabeth II to Chile in 1968, are the highpoints of a complex relationship. Under "West Europe" will be considered England, France, West Germany, plus Spain, which has been always seen be Chileans as part of a certain West Europe. The research has been done in Chilean, as well English, French, German and Spanish archives.